Encyclopedia of Radicals in Chemistry, Biology and Materials 2012
DOI: 10.1002/9781119953678.rad026
|View full text |Cite
|
Sign up to set email alerts
|

The S RN 1 Reaction

Abstract: Since its discovery, the radical nucleophilic substitution, or S RN 1 reaction, has been widely used to achieve new CC or C‐heteroatom bonds. The mechanism involves a chain propagation cycle with radicals and radical anions as intermediates. The initiation step is an electron transfer to a substrate to form its radical anion, which fragments to afford a radical and the anion of the leaving group. The radical thus formed couples with a nucleophile to give a new radical anion which, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 168 publications
0
14
0
2
Order By: Relevance
“…[135] Theinitiation of the BHAS reaction was also reported by other photoactivation modes,f or example, through PET from an iridium sensitizer to R-X, or upon excitation with light of an in situ formed photosensitive complex between KO t Bu and phenanthroline. [136,137] Nonnucleophilic bases are commonly employed to avoid the competing S RN 1r eaction pathway.L ight-mediated substitutions following the S RN 1r eaction with organic anions as nucleophiles have been studied extensively and were the subject of recent reviews [4,134,[138][139][140][141][142] and thus will not be further discussed herein.…”
Section: Organic Anions Promoting the Radical-nucleophilic Substitutimentioning
confidence: 99%
“…[135] Theinitiation of the BHAS reaction was also reported by other photoactivation modes,f or example, through PET from an iridium sensitizer to R-X, or upon excitation with light of an in situ formed photosensitive complex between KO t Bu and phenanthroline. [136,137] Nonnucleophilic bases are commonly employed to avoid the competing S RN 1r eaction pathway.L ight-mediated substitutions following the S RN 1r eaction with organic anions as nucleophiles have been studied extensively and were the subject of recent reviews [4,134,[138][139][140][141][142] and thus will not be further discussed herein.…”
Section: Organic Anions Promoting the Radical-nucleophilic Substitutimentioning
confidence: 99%
“…These mild conditions are quite different from the challenge S N 1 or S N 2 substitution of difluoroalkyl halides, because of the difficulty in forming a difluoroalkyl carbocation (S N 1) or the repulsion of the lone pairs of fluorine atoms to the carbon nucleophile (S N 2). 18 This difference implies a novel mechanism, which is discussed below. Encouraged by these results, we tested a series of reaction parameters (for details, see the ESI†), and found that the use of 3.0 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…Lichtvermittelte Substitutionsreaktionen, die nach dem S RN 1-Mechanismus verlaufen, wurden weitreichend untersucht und sind Gegenstand von Buchkapiteln und neueren Aufsätzen, weshalb wir hier nicht weiter auf sie eingehen. [4,134,[138][139][140][141][142]…”
Section: Donor-akzeptor-komplexe Organischer Anionenunclassified